FORMULATION OF BRIGHTENING GEL WITH ETANOL EXTRACT OF RED PAWPAW LEAVES (Syzygium oleana) AS ANTIOXIDANT - Suryanita; Alfiani Am, Fenni; Asri SR, Muhammad; junita, Nurfitria (Journal of Pharmaceutical Science and Herbal Technology, 2024)
Excessive sun exposure can have a negative impack on the skin. One way that can be done to reduce this impact is to use sunscreen. This research aimed to determine whether the ethanol of red shoot leaves (Syzygium oleana) can be formulated into a gel preparation that is physically and chemically stable and to determine sunscreen activity based on the SPF value using the UV-VIS spectrophotometric method. The method in this research was laboratory experimental. Red shoot leaves were extracted by using the maceration method with a preparation formula designe in three concentration, namely Formula 1 (1%), Formula 2 (3%),and  Formula 3 (5%). Then a stability test was carried out by storing at temperatures of 40C and 400C. Evaluation of preparation qualityincludes organoleptic, homogeneity, pH, viscosity, and spreadability test. An SPF value test was also carried out. The research results that have been carried out show that the ethanol extract of red shoot leaves with concentration of 1% 3% and 5% formulated in gel form produces a stable preparation and meets the quality requirements of the preparation. The SPF value from formula 1 is 2,508349 (minimal protection), formula 2 3,380475 (minimal protection) and formula 3 2,679704 (minimal protection).